2021
DOI: 10.1126/science.abj4290
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid radical-polar pathway for excision of ethylene from 2-oxoglutarate by an iron oxygenase

Abstract: Microbial ethylene-forming enzyme (EFE) converts the C3-C4 fragment of the ubiquitous primary metabolite, 2-oxoglutarate (2OG), to its namesake alkene product. This reaction is very different from the simple decarboxylation of 2OG to succinate promoted by related enzymes and has inspired disparate mechanistic hypotheses. We show that EFE produces stereochemically random (equal cis and trans) 1,2-[2H2]-ethylene from (3S,4R)-[2H2]-2OG, appends an oxygen from O2 upon the C1-derived (bi)carbonate, and can be diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 30 publications
(83 reference statements)
4
34
0
Order By: Relevance
“…Bollinger and Krebs first experimentally established the key Fe­(IV)O oxidant in 2003 . The nonheme Fe­(IV)O in this supergroup of enzymes is a powerful oxidant for which whose action results in a wide range of oxidative outcomes such as hydroxylation, desaturation, epimerization, epoxidation, ring closure, ring expansion, and C–C or C–N bond-coupling reactions. ,,,, Because of their versatility, these enzymes have several important roles in biological processes, including the post-translational modification of collagen, fatty acid metabolism, oxygen sensing, DNA and RNA repair, ethylene production, and the biosynthesis of many antibiotics. ,,, …”
Section: Oxygenation Reactions With α-Ketoglutarate As a Cosubstratementioning
confidence: 99%
“…Bollinger and Krebs first experimentally established the key Fe­(IV)O oxidant in 2003 . The nonheme Fe­(IV)O in this supergroup of enzymes is a powerful oxidant for which whose action results in a wide range of oxidative outcomes such as hydroxylation, desaturation, epimerization, epoxidation, ring closure, ring expansion, and C–C or C–N bond-coupling reactions. ,,,, Because of their versatility, these enzymes have several important roles in biological processes, including the post-translational modification of collagen, fatty acid metabolism, oxygen sensing, DNA and RNA repair, ethylene production, and the biosynthesis of many antibiotics. ,,, …”
Section: Oxygenation Reactions With α-Ketoglutarate As a Cosubstratementioning
confidence: 99%
“…[21][22][23][24][25][26] Upon dioxygen activation in the presence of substrate and co-substrate 2OG, [27][28][29][30][31][32][33][34][35] the wellcharacterized ferryl-oxo active species can be generated to initiate the reaction via either hydrogen atom abstraction from the substrate or oxygen atom transfer to the substrate. [15,[36][37][38][39][40][41][42][43][44][45][46][47][48] As the first Fe/2OG-dependent endoperoxidase,t he mechanism of FtmOx1 remains elusive at current stage.L i and co-authors performed isotopic experiments and demonstrated that both oxygen atoms inserted into the structure of verruculogen arise from as ingle O 2 molecule. [9] They also found that ascorbate was essential for the enzymatic endoperoxide conversion by FtmOx1.…”
Section: Introductionmentioning
confidence: 99%
“…This family of enzymes employ a conserved 2‐His‐1‐carboxylate facial triad in the active pocket to coordinate a ferrous iron cofactor [21–26] . Upon dioxygen activation in the presence of substrate and co‐substrate 2OG, [27–35] the well‐characterized ferryl–oxo active species can be generated to initiate the reaction via either hydrogen atom abstraction from the substrate or oxygen atom transfer to the substrate [15, 36–48] …”
Section: Introductionmentioning
confidence: 99%
“…EFE generally catalyzes two reactions: (a) the oxidative decarboxylation of αKG to form a succinate concomitant with C 5 -hydroxylation of l -arginine, where the hydroxyarginine intermediate is decomposed to guanidine, and (b) the conversion of αKG into ethylene and three molecules of CO 2 . ,,, Kinetic studies with l -Arg versus deuterated l -Arg proposed that the l -Arg hydroxylation pathway proceeds via an iron­(IV)-oxo intermediate (Figure , right), while the kinetics of ethylene formation are not affected by deuteration of l -Arg. , They concluded, therefore, that the ethylene formation does not pass an iron­(IV)-oxo species and diverges from the l -arginine hydroxylation pathway at an earlier stage and possibly is formed from the conversion of the iron­(III)-superoxo species into a peroxic anhydride complex (bottom-right structure in Figure ). Nevertheless, l -arginine plays a critical role in the ethylene formation reaction catalyzed by EFE .…”
Section: Introductionmentioning
confidence: 99%